Abnormal osteopontin and matrix extracellular phosphoglycoprotein localization, and odontoblast differentiation, in X-linked hypophosphatemic teeth. (August 2014) - Salmon, B.; Bardet, C.; Coyac, B. R.; Baroukh, B.; Naji, J.; Rowe, P. S.; Opsahl Vital, S.; Linglart, A.; Mckee, M. D.; Chaussain, C.
Abstract Mutations in phosphate-regulating gene (PHEX) lead to X-linked hypophosphatemic rickets (XLH), a genetic disease characterized by impaired mineralization in bones and teeth. In human XLH tooth dentin, calcospherites that would normally merge as part of the mineralization process are separated by unmineralized interglobular spaces where fragments of matrix proteins accumulate. Here, we immunolocalized osteopontin (OPN) in human XLH teeth, in a three-dimensional XLH human dental pulp stem cell-collagen scaffold culture model and in a rat tooth injury repair model treated with acidic serine- and aspartate-rich motif peptides (ASARM). In parallel, matrix extracellular phosphoglycoprotein (MEPE) immunolocalization and alkaline phosphatase (ALP) activity were assessed in XLH teeth. OPN was expressed by odontoblasts in the XLH models, and localized to the abnormal calcospherites of XLH tooth dentin. In addition, ALP activity and MEPE localization were abnormal in human XLH teeth, with MEPE showing an accumulation in the unmineralized interglobular spaces in dentin. Furthermore, XLH odontoblasts failed to form a well-polarized odontoblast layer. These data suggest that both MEPE and OPN are involved in impaired tooth mineralization associated with XLH, possibly through different effects on the mineralization process.